The Stagnation of Weaving Artisans: Uncovering the Causes of Minimal Youth Involvement in Loyok - Hilmiyatun; Baiq Gina Haqiqah; Zainul Arifin; Alia Ramadani; Aldi Zuniardi; Napiza Janhurrahmi (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This study aims to analyse the factors causing the weakening of bamboo weaving artisan regeneration in Loyok Village, Sikur Subdistrict, East Lombok Regency, and its implications for the sustainability of the local culture-based creative economy. The study uses a qualitative approach with a descriptive type. Informants were selected purposively, including senior craftsmen, young craftsmen, young non-craftsmen, BUMDes administrators, and village officials. Data were collected through semi-structured interviews, observation, and documentation, then analysed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, and tested for validity using trustworthiness criteria. The results showed that the weakening of artisan regeneration was influenced by several main factors, namely: shifts in socio-cultural values that made the artisan profession no longer prestigious; low motivation among the younger generation, who were more interested in modern jobs with a fixed salary; economic barriers in the form of unstable income, rising raw material prices, limited capital, and narrow market access; and institutional support that is not yet sustainable. On the other hand, technological innovation and digital marketing are beginning to open up new opportunities for young artisans, although they are still constrained by a digital skills gap. This study emphasises the need for a comprehensive strategy that integrates economic strengthening, design innovation, digital marketing, and strengthening the role of village institutions to support the regeneration of artisans in Loyok Village.